Analisis Representasi Nilai Nilai Pancasila dalam Karya Seni Rupa: Lukisan Laskar Rakyat Mengatur Siasat Karya Affandi - Nova Ritonga; Mey Waty Aulia; Intan Mumtazah Assaa’idah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to analyze the representation of Pancasila values ​​in the painting Laskar Rakyat setting Siasat by Affandi. This painting is considered to have a strong philosophical meaning related to the struggle of the Indonesian people in maintaining independence. This study uses a qualitative method with a literature study approach (library research), where data is obtained from various written sources such as books, scientific journals, articles, and related documents. The data collection technique is carried out through the documentation method, while the data obtained is analyzed using content analysis techniques to identify symbols, colors, and visual elements that reflect the values ​​of Pancasila. The results of the study show that the painting Laskar Rakyat setting Siasat represents the five values ​​of Pancasila. The value of Belief in the One Almighty God is seen in the slogan "Once Independent, Always Independent" which reflects the belief that independence is a gift from God. The value of Just and Civilized Humanity is seen in the solidarity of the fighters without distinguishing backgrounds. The value of Indonesian Unity is realized through the togetherness of the fighters who develop a joint strategy. The value of Democracy Led by the Wisdom of Deliberation and Representation is depicted in the discussion scene among the fighters. Finally, the value of Social Justice for All Indonesian People is reflected through the painting of simple war equipment that shows the struggle of the common people in maintaining independence. This study confirms that works of art, especially Affandi's paintings, are able to be an effective medium in conveying moral messages, values ​​of friendship, and the spirit of struggle.